1999
DOI: 10.1071/a98051
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the risk associated with drying-off strategies for irrigated sugarcane before harvest

Abstract: The development of recommendations for drying-off management in sugarcane is difficult due to climatic variability and lack of knowledge of the sensitivity of changes in sucrose content and cane yield to severity of water deficit. Relative cane biomass targets were developed for drying-off irrigated sugarcane before harvest based on derived relationships between cane yield, cane dry weight, and sucrose concentration, using pooled data from previous field studies. These targets were then linked to a crop–soil m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 1 publication
2
24
1
6
Order By: Relevance
“…The maximum LAI values observed in this study were higher than that observed in sugarcane plants (4.92) by Robertson et al (1999), and those obtained under full irrigation at 152 DAP (6.82), and without irrigation at 147 DAP (6.80) by Farias et al (2008). Additionally, Oliveira et al (2004) reported a maximum of 4.8 and 5.8 for varieties RB72454 and RB855113, respectively, at 377 DAP, and 4.5 at 323 DAP for the variety RB855536.…”
Section: Resultscontrasting
confidence: 47%
“…The maximum LAI values observed in this study were higher than that observed in sugarcane plants (4.92) by Robertson et al (1999), and those obtained under full irrigation at 152 DAP (6.82), and without irrigation at 147 DAP (6.80) by Farias et al (2008). Additionally, Oliveira et al (2004) reported a maximum of 4.8 and 5.8 for varieties RB72454 and RB855113, respectively, at 377 DAP, and 4.5 at 323 DAP for the variety RB855536.…”
Section: Resultscontrasting
confidence: 47%
“…In South Africa, Robertson and Donaldson (1998) reported that the practice of drying-off before harvest increased sucrose content by 18%. Furthermore, Robertson et al (1999) analyzed 37 drying-off experiments during 1965 and 1995. Out of 83 experiments on the drying-off treatments analyzed, 19 experiments increased sucrose yield between 0.5 and 2.5 t ha 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Robertson et al (1999) showed that SC on a fresh mass basis remained higher in dry-down treatments than fully irrigated treatments, even when the cane yield in the dry-down treatments had been reduced by as much as 50% by water stress. Conversely, misunderstanding of the ripening response could lead to losses in sucrose yield.…”
Section: Water Stressmentioning
confidence: 96%